Peningkatan Kapasitas Produksi dan Pemasaran Produk Olahan Kelapa dan Susu menjadi Sup Buah - Gobel, Yusriyah Atikah; Mokoolang, Susan; Djibran, Moh. Muchlis; Fahrullah, Fahrullah (Jurnal Pengabdian Magister Pendidikan IPA, 2024)
Healthy snack-making is a home-based business that many people in Gorontalo Regency engage in. The significant demand for such snacks presents a promising business opportunity. With stiff competition, it's necessary for these businesses to continuously strive for innovation and breakthroughs to ensure their products remain in high demand with consumers. The aim of this initiative is to enhance the local community's understanding of managing their business in a professional, creative and innovative way, and to broaden the exposure of their products in the market. The aim of this initiative is to enhance the local community's understanding of managing their business in a professional, creative and innovative way, and to broaden the exposure of their products in the market. These objectives will be achieved through a range of community service activities such as lectures, practical demonstrations of fruit soup preparation, step-by-step guidance, and assessment. The community service project was well received by the partners, as evidenced by their active participation in all stages of the initiative. Both partners benefitted from this activity, particularly in the areas of marketing, business management, and capacity building.